Media and political campaigns for individual pairs of regional election winners in Rejang Lebong regency in 2020 during the Covid-19 pandemic - Akbar Brilian Utama; Pawito Pawito; Ignatius Agung Satyawan (Informasi, 2022)
The 2020 elections were held for the first time during the COVID-19 pandemic, this also had an impact on campaign activities as it is known that during the pandemic all outdoor activities were limited. This study aims to find out what kind of campaigns were carried out and the media used by the winning individual pairs and their team in the 2020 Local Leaders Election of Rejang Lebong during pandemic. This study applied a qualitative method with a constructivism paradigm. The research subjects are individual pairs and supporting teams. Data collection technique is in the form of interviews and documentation. This research applied Nowak and Warneryd’s campaign model to explain this phenomenon. From the results of the study it can be concluded that the campaign is not much different from the previous Local Leaders Election but the use of social media is very important in the campaign during the pandemic because all activities are limited, therefore social media has an important role during the campaign period and the media used in the campaign, namely: social media such as Facebook, Whatsapp, and Instagram.